A GFP Reporter MR766-Based Flow Cytometry Neutralization Test for Rapid Detection of Zika Virus-Neutralizing Antibodies in Serum Specimens - Frumence, Etienne (Vaccines (Basel), 2019)
Zika virus (ZIKV) is an emerging arthropod-borne virus of major public health concern. ZIKV infection is responsible for congenital Zika disease and other neurological defects. Antibody-mediated virus neutralization is an essential component of protective antiviral immunity against ZIKV. In the present study, we assessed whether our GFP reporter ZIKV derived from African viral strain MR766 could be useful for the development of a flow cytometry neutralization test (FNT), as an alternative to the conventional plaque-reduction neutralization test (PRNT). To improve the efficacy of GFP-expressing MR766, we selected virus variant MR766(GFP) showing a high level of GFP signal in infected cells. A MR766(GFP)-based FNT was assayed with immune sera from adult mice that received ZIKBeHMR-2. The chimeric ZIKV clone ZIKBeHMR-2 comprises the structural protein region of epidemic strain BeH819015 into MR766 backbone. We reported that adult mice inoculated with ZIKBeHMR-2 developed high levels of neutralizing anti-ZIKV antibodies. Comparative analysis between MR766(GFP)-based FNT and conventional PRNT was performed using mouse anti-ZIKBeHMR-2 immune sera. Indistinguishable neutralization patterns were observed when compared with PRNT(50) and FNT(50). We consider that the newly developed MR766(GFP)-based FNT is a valid format for measuring ZIKV-neutralizing antibodies in serum specimens.